2015
DOI: 10.3233/jpi-2009-0179
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial tracheitis – tremendously rare, but truly important: A systematic review

Abstract: Bacterial tracheitis is a rare, but potentially life-threatening infection, which predominately affects children. The existing literature on this condition is relatively limited. Objective: To provide a comprehensive review of the published literature on bacterial tracheitis by systematically summarizing epidemiological, radiological, clinical and microbiological aspects of the disease combined with a discussion of potential mechanisms involved in the pathogenesis and recommendations for the management of susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The clinical course of patients in this study was consistent with recently published reports suggesting a spectrum in the severity of disease. 1-3,6-11 Patients diagnosed and treated for bacterial tracheitis at our institution were more likely to be privately insured, and white. Further study of bacterial tracheitis should focus on the spectrum of severity and a broader analysis of patient demographics over a larger geographic area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical course of patients in this study was consistent with recently published reports suggesting a spectrum in the severity of disease. 1-3,6-11 Patients diagnosed and treated for bacterial tracheitis at our institution were more likely to be privately insured, and white. Further study of bacterial tracheitis should focus on the spectrum of severity and a broader analysis of patient demographics over a larger geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the presentation, bacteriology, clinical course, and outcomes found in this series were consistent with previous literature on pediatric bacterial tracheitis. [1][2][3][4][5][6][7][8][9][10][11] Along with clinical outcomes, we examined the demographic characteristics of patients with a diagnosis of bacterial tracheitis, and found that children diagnosed with bacterial tracheitis were more likely to be privately insured than a control group. This suggests that children of higher SES are more likely to be diagnosed and treated for bacterial tracheitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that define the optimal treatment of bacterial tracheitis within the pediatric population are limited. 15 In addition, the optimal treatment duration with nebulized antibiotics also remains unclear. For the treatment with systemic therapies, studies recommend 10-to 14-day treatment courses.…”
Section: Discussionmentioning
confidence: 99%